2010
DOI: 10.1007/s00595-009-4166-7
|View full text |Cite
|
Sign up to set email alerts
|

Collision tumor of primary malignant lymphoma and adenocarcinoma in the colon: Report of a case

Abstract: This report presents the case of a 62-year-old man with a collision tumor of primary malignant lymphoma and adenocarcinoma in the cecum. All regional mesenteric lymph nodes that were removed surgically were found to be occupied by lymphoma cells and no lymph nodes contained any cancer cells, although the primary carcinomas did exhibit lymphatic invasion. Malignant lymphoma was also seen in the duodenum. Systemic chemotherapy was administered for the malignant lymphoma, and a complete response was thus obtained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 16 publications
(16 reference statements)
0
25
0
Order By: Relevance
“…Previous reports have been limited because of the rarity of such collision tumors, and most reports did not describe the course of the disease after diagnosis. Sasaki et al [6] reported that a patient received six courses of combined chemotherapy (cyclophosphamide, doxorubicin, vincristine, and prednisone regimen with rituximab) against malignant lymphoma, which yielded a complete response. In our case, the patient underwent six courses of chemotherapy with mFOLFOX6 followed by capecitabine to treat sigmoid colon adenocarcinoma with lung metastasis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports have been limited because of the rarity of such collision tumors, and most reports did not describe the course of the disease after diagnosis. Sasaki et al [6] reported that a patient received six courses of combined chemotherapy (cyclophosphamide, doxorubicin, vincristine, and prednisone regimen with rituximab) against malignant lymphoma, which yielded a complete response. In our case, the patient underwent six courses of chemotherapy with mFOLFOX6 followed by capecitabine to treat sigmoid colon adenocarcinoma with lung metastasis.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, colon lymphomas represent 5.6% to 20% of all gastrointestinal lymphomas [10]. Furthermore, lymphoma synchronously accompanied by adenocarcinoma of the colon is extremely rare [6]. …”
Section: Introductionmentioning
confidence: 99%
“…Our literature search identified nine case reports in which detailed morphological characteristics were described and endoscopic images were presented (Table 2) (2, 18-25). Among the reported cases, Sasaki et al described a patient with a collision tumor of follicular lymphoma and adenocarcinoma in the cecum (22). In this patient, a large tumor (15 cm) was seen by colonoscopy, but the pathological examinations of the resected specimen revealed the adenocarcinoma component to be predominant.…”
Section: Discussionmentioning
confidence: 91%
“…To our knowledge, there are fifteen cases of this type of collision to date, including this report (Table 1) [9][10][11][12][13][14][15][16][17][18][19][20][21][22]. There is a male and elderly predominance at an average age The majority of collisions arise in the cecum or rectum, with eight arising from the right colon, one from the transverse colon, and six from the left colon.…”
Section: Discussionmentioning
confidence: 99%